Spice Route Activities As a Development Strategy Sustainable Tourism - Siregar, Aisyah Astinadia; Mokhtar, Nur Afiqa Binti (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
All development activities in the tourism strategy will be able to be used or synergized with tourism activities. Tourism activities can be a solution to get people out of poverty. Several regions have succeeded in using tourism to develop their regions. However, the use of tourism resources must also be in line with sustainable development, including tourism based on local culture and empowerment of community groups. History also shows that in the past, Indonesian waters played an important role in the navigation of local people's ships and foreign ships in the flow of trade traffic, cultural diplomacy and the spread of religion. Through sustainable tourism development, apart from increasing its attractiveness, it is also able to support strengthening efforts to preserve the natural and cultural environment in the region or destination. The existence of the Spice Route program, with its advantages and disadvantages, has opened up opportunities for sustainable tourism through the concept of marine tourism as a tool that can provide inspiration, memory or collective awareness of the long history of the formation of national civilization. Apart from that, the Spice Route program as a national program is an effort to reconstruct trade routes for commodities, especially spices, between tribes and nations in the past, which placed Indonesia as the axis of world commerce and at the same time opened Indonesia to world civilization. One active participation in tourism is to raise the attractiveness of areas along the Spice Route as Indonesian tourist destinations based on maritime and agricultural cultural roots. This research is qualitative research with an approach used based on literature studies. From this research, it is concluded that sustainable tourism development requires a comprehensive community involvement strategy from all stages of development, from the planning stage to the implementation of development.